Peningkatan Kesadaran tentang Kebersihan Lingkungan melalui Pengelolahan Sampah Berbasis Edukasi di Kalangan Mahasiswa - Lestari, Utami Puji; Putra, Arya Hidayat; Munir, Misbachul; El-Yunusi, Muhammad Yusron; Ernawati (Jurnal Pengabdian Kepada Masyarakat, 2026)
This activity aims to raise public awareness through an education-based waste management program implemented at Sunan Giri University of Surabaya as an effort to foster environmental awareness within the campus community. The main problem identified was the low level of knowledge and concern regarding proper waste sorting, management, and disposal, which resulted in waste accumulation, unpleasant odors, and potential flooding risks. This program employed the Participatory Action Research (PAR) method, involving students and surrounding community members directly in observation, discussions, problem mapping, and the determination of priority actions. Practical activities included sorting organic and inorganic waste, cleaning campus areas, removing wild grass, providing waste management education, and practicing simple recycling techniques. The results indicated an increase in participants’ understanding as well as positive behavioral changes, such as disposing of waste properly, implementing waste sorting, and actively participating in routine cleanliness activities. Overall, this program proved effective in building a culture of cleanliness, strengthening social responsibility, and reinforcing the notion that campus cleanliness is an essential part of shared ecological awareness. Furthermore, this activity facilitated collaboration between students and the surrounding community, thereby fostering harmonious social relations.